2021
DOI: 10.4028/www.scientific.net/msf.1038.352
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Bitumen-Polymer Composition, Resistant to Atmospheric Influences, Based on Petroleum Bitumen and their Properties Study

Abstract: In the work the bituminous-polymeric composition stable against action of external factors is designed taking into account literature-patent researches and industrial needs. The basic physical-mechanical and thermophysical properties of the designed bituminous-polymeric composition are investigated, and also change of water absorption, shrinkage with time and flammability is studying. The technology of manufacturing bitumen-polymer composition in production is described. The designed bituminous-polymeric compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…This observation is due to the free space, wave resistance mismatch, and decreased RAM efficiency in the material. The design of products from polymeric materials is a very difficult task in terms of creating new polymeric materials, because it requires appropriate technological and design information, for the developed wares, equipment for their manufacture, as well as different technological parameters of their processing [16,17,18]. So, when designing RAM, two main tasks must be solved: (i) To attain the apparent dielectric constant values which will provide the maximum possible absorption coefficient; (ii) To ensure the equality between material effective input resistance and the wave resistance of the environment in which the incident EMR propagates, i.e., to match the material with the external environment [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…This observation is due to the free space, wave resistance mismatch, and decreased RAM efficiency in the material. The design of products from polymeric materials is a very difficult task in terms of creating new polymeric materials, because it requires appropriate technological and design information, for the developed wares, equipment for their manufacture, as well as different technological parameters of their processing [16,17,18]. So, when designing RAM, two main tasks must be solved: (i) To attain the apparent dielectric constant values which will provide the maximum possible absorption coefficient; (ii) To ensure the equality between material effective input resistance and the wave resistance of the environment in which the incident EMR propagates, i.e., to match the material with the external environment [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work it was found that the modification of bitumen by different thermoplastics and phospholipids is effective [7,8]. The designed in [8] bituminous-polymeric composition has the following indicators: melting temperature -120 °С; heat resistance for 2 hours -118 °С; water absorption -0.7 %; impact strength -6.9 MPa; shrinkage -0.12 %.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work it was found that the modification of bitumen by different thermoplastics and phospholipids is effective [7,8]. The designed in [8] bituminous-polymeric composition has the following indicators: melting temperature -120 °С; heat resistance for 2 hours -118 °С; water absorption -0.7 %; impact strength -6.9 MPa; shrinkage -0.12 %. Today, considerable experience has been gained abroad in the use in the construction and road coatings repair composite materials based on bitumen and polymer modifiers in the form of polymer elastomers and rubber crumbs.…”
Section: Introductionmentioning
confidence: 99%
“…Наведемо аналіз адгезійних властивостей бітумів, модифікованих смолою бурого вугілля, за методикою визначення зчеплення в'яжучого з поверхнею мінерального матеріалу (рис. [1][2][3][4].…”
unclassified